Psychosocial strategies in telehealth for mental health management: A scoping review - Maulana, Indra; Sakhi Fadila, Salsabila (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Despite telemedicine being a significant instrument for mental health management, psychological and social factors such as stigma and lack of desire frequently hinder patient engagement. Although psychological methods demonstrate potential in addressing these disorders, comprehensive evidence remains limited as of May 2025. Purpose: To delineate psychosocial strategies in telehealth that enhance patient engagement with mental health disorders, evaluate their impact, and identify challenges and research gaps. Method: This work employs a scoping review and article selection methodology in accordance with the PRISMA-ScR criteria, utilizing a literature search. Boolean approaches were employed to search PubMed, Scopus, PsycINFO, IEEE Xplore, and Web of Science from 2015 to 2025. The inclusion criteria consist of studies on psychosocial therapies for adult individuals with mental health disorders. Ten actual papers from an anticipated forty served as the foundation for thematic analysis of the material. Results: User-friendly interfaces, empathy-driven chatbots,gamification, AI personalization, motivational reminders, and virtual communities contribute to enhanced therapy adherence (15–30%), increased session frequency (20–30%), elevated patient satisfaction (75–88%), and reduced service dropout (10–15%). The challenges encompass inadequate digital literacy, technological costs, data privacy concerns, cultural resistance, and insufficient infrastructure. Research gaps encompass the lack of studies on vulnerable populations, long-term effects, cultural differences, and significant disruptions. Conclusion: The psychosocial approach in telehealth effectively enhances patient engagement by addressing emotional, cognitive, and social needs, hence fostering community health empowerment. However, to optimize its efficacy, one must address implementation challenges and research gaps. Keywords: Psychosocial Approach; Patient Engagement; Telehealth.